Die Macht der Wirkungsannahmen : Medienarbeit des britischen und deutschen Militärs in der ersten Hälfte des 20. Jahrhunderts - Götter, Christian (2015)
The collaboration between the military and the media that we know today was developed in the first half of the 20th century. This study shows that military leaders were primarily interested in the media because they hoped to achieve objectives that would otherwise be beyond their capacities: they wanted to influence populations, parliaments, and governments - in times of war and peace.